2019
DOI: 10.3390/ijms20040795
|View full text |Cite
|
Sign up to set email alerts
|

Increased TGF-β and BMP Levels and Improved Chondrocyte-Specific Marker Expression In Vitro under Cartilage-Specific Physiological Osmolarity

Abstract: During standard expansion culture (i.e., plasma osmolarity, 280 mOsm) human articular chondrocytes dedifferentiate, making them inappropriate for autologous chondrocyte implantation to treat cartilage defects. Increasing the osmolarity of culture media to physiological osmolarity levels of cartilage (i.e., 380 mOsm), increases collagen type II (COL2A1) expression of human articular chondrocytes in vitro, but the underlying molecular mechanism is not fully understood. We hypothesized that TGF-β superfamily sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Timur et al attempted to dissect the mechanism underlying the chondrogenic effect of physiological osmolarity on in vitro cultured human articular cartilage chondrocytes [21]. While normal expansion culture medium with plasma osmolarity (280 mOsm) induces chondrocyte dedifferentiation, higher levels of oxygenation mimicking physiological osmolarity of the healthy cartilage (in a range of 380-450 mOsm) favors the elevated expression of the chondrogenic marker gene COL2A1.…”
Section: Oa and Physiological Microenvironmentmentioning
confidence: 99%
“…Timur et al attempted to dissect the mechanism underlying the chondrogenic effect of physiological osmolarity on in vitro cultured human articular cartilage chondrocytes [21]. While normal expansion culture medium with plasma osmolarity (280 mOsm) induces chondrocyte dedifferentiation, higher levels of oxygenation mimicking physiological osmolarity of the healthy cartilage (in a range of 380-450 mOsm) favors the elevated expression of the chondrogenic marker gene COL2A1.…”
Section: Oa and Physiological Microenvironmentmentioning
confidence: 99%
“…To assess the effect of physoxia on the chondrocytic phenotype, we screened the expression of ECM markers associated with a differentiated (i.e., wanted) and de-differentiated (i.e., unwanted, fibroblastic) phenotype of articular chondrocytes. We used the expression of the core protein of aggrecan ( ACAN ), an important proteoglycan (PG) of the ECM of articular chondrocytes, and that of the structural key marker protein collagen type II ( COL2A1 ) [37], as indicators of a proper phenotype (Figure 2). Expression of both genes showed an inverse pO 2 -dependency, up-regulation of mRNA abundances with down-regulated pO 2 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Ordering details and instructions for using the TGF-β2-specific ELISA assay can be found elsewhere [37]. Briefly, medium was collected and centrifuged at 1200 rpm for 8 min to remove cell debris.…”
Section: Methodsmentioning
confidence: 99%
“…GAG-bound TGF-β is able to stimulate neocartilage formation ( Park et al, 2008 ) and it was recently shown that under cartilage physiological osmolarity TGF-β signaling was increased. This was associated with an improved chondrocyte phenotype ( Tan Timur et al, 2019 ). Indeed, also in our studies we observed increased (but not significant) TGF-β3 expression in the Aggrecan-supplemented conditions.…”
Section: Discussionmentioning
confidence: 99%